PEMANFAATAN FLY ASH-BOTTOM ASH (FABA) SEBAGAI CAMPURAN MEDIA TANAM TERHADAP PERTUMBUHAN, HASIL DAN KUALITAS TOMAT - Anita Azima Putri; Jon Yawahar (Agriculture, 2023)
Fly ash and bottom ash are the remains of coal combustion whose production is abundant, but its processing is not maximum. Therefore, FABA should be optimally utilized as a mixture of vegetable growing media. The study aims to test the use of FABA as a mixture of plant media against vegetable growth, yield, and nitrate content. The research was conducted at …. The research were arrennged in RCBD with two factors, the first factor is the composition of the planting media consisting of 4 levels, i.e. (K0) = 0 kg FABA + land 16,0 kg, (K1) = Fly ash 0,4 kg + bottom ash 0,1 kg + land 15,50 kg; (K2) = Fly Ash 0,8 kg + lower ash 0,2 kg + ground 15,0 kg (K3) = Fly ash 1,2 kg + bottom ash 0,3 kg + tanah 14,50 kg. The results showed The composition of the planting medium 0.8 kg FA + 0.2 kg BA + 16 kg soil gave the best response to the variable number of fruit, fruit weight per plant, fruit diameter and fruit hardness. The highest nitrate content was obtained from the composition of the planting medium 0 kg FABA + 16 kg soil, while the lowest nitrate content was 1.2 kg FA + 0.3 BA + 14.5 kg soil. Vegetable products are safe for consumption in terms of nitrate levels consumed based on the provisions of the Accetable Daily Intake (ADI) and Estimated Daily Intake (EDI) Keywords : fly ash, bottom ash, nitrate, vegetable, acceptable daily intake